Defining treatment‐resistant depression. Issue 2 (22nd October 2019) - Gaynes, Bradley N.; Lux, Linda; Gartlehner, Gerald; Asher, Gary; Forman‐Hoffman, Valerie; Green, Josh; Boland, Erin; Weber, Rachel P.; Randolph, Charli; Bann, Carla; Coker‐Schwimmer, Emmanuel; Viswanathan, Meera; et al.
Abstract: Background: Varying conceptualizations of treatment‐resistant depression (TRD) have made translating research findings or systematic reviews into clinical practice guidelines challenging and inconsistent. Methods: We conducted a review for the Centers for Medicare & Medicaid Services and the Agency for Healthcare Research and Quality to clarify how experts and investigators have defined TRD and to review systematically how well this definition comports with TRD definitions in clinical trials through July 5, 2019. Results: We found that no consensus definition existed for TRD. The most common TRD definition for major depressive disorder required a minimum of two prior treatment failures and confirmation of prior adequate dose and duration. The most common TRD definition for bipolar disorder required one prior treatment failure. No clear consensus emerged on defining adequacy of either dose or duration. Our systematic review found that only 17% of intervention studies enrolled samples meeting the most frequently specified criteria for TRD. Depressive outcomes and clinical global impressions were commonly measured; functional impairment and quality‐of‐life tools were rarely used. Conclusions: Two key steps are critical to advancing TRD research: (a) Developing a consensus definition of TRD that addresses how best to specify the number of prior treatment failures and the adequacy of dose and duration; and (b) identifying a core package of outcome measures that can be applied in a standardized manner. Our recommendations about stronger approaches to designing and conducting TRD research will foster better evidence to translate into clearer guidelines for treating patients with this serious condition.